Do We Have Enough Laws To Prevent Stalking In India? - Jain, Naman (Trinity Law Review, 2021)
Stalking is a step one offence which leads to the occurrence of the serious and heinous crimes  such as rape and outraging modesty of a woman. The laws related to stalking is weak in India  and people are not aware about the fact of zero FIR and the mindset of the offender. How  Bollywood and cinema is helping in making the psychology weak and affect the society at large.  The statistics from various researches and reports show that woman remains silent and which  causes them various problems and disorders. Also, the article discusses about the laws  available for the woman under IPC,1860 and how they are modified and government’s take on  this to improve the situation and laws for the woman. In Indian constitution woman are given  a special status keeping the historical background in consideration which makes the laws  favoring the women. The author puts some suggestions and his finding to curb the problem in  the country.
Keywords: occurrence; heinous; FIR; Bollywood; psychology; IPC